PEMBUATAN MINUMAN SEDUH DAUN KERSEN (Muntigia Calabura. L) DENGAN PENAMBAHAN DAUN STEVIA (Stevia Rebaudiana) SEBAGAI PEMANIS ALAMI RENDAH KALORI - M. Tahir, Mulyati; Bilang, Mariyati; Nurmitasari, Nurmitasari (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2017)
Drinks combination of cherry leaves and dried stevia leaves can be used as a health drink contains antioxidants and low-calorie sugar. This study aims to get types proper drying in the manufacture of beverages so that the antioxidant content is not damaged and lost. Analysis was conducted on the analysis of sensory, physicochemical and microbiological testing. The design methods Completely Randomized Design (CRD) with 2 factorial. The first factor is the addition of stevia leaf dry consisting of 4 levels (0%, 25%, 50% and 75%), the second factor is the type of drying which consists of two type of (drying by oven blowers and drying by oven vacuum), while the vacuum drying the best in terms of sensory analysis (color, aroma, and taste) and antioxidant activity of 77.8%, brewed beverage formulations obtained by the treatment of dry cherry leaves 75% and 25% of dry stevia leaves with the results of sensory analysis (color, aroma and flavor) rather liking, the antioxidant activity of 78.5%, and total calories of 2.9 kcal.Keywords: cherry leaves, stevia, brewed beverages, low calorie beverages and antioxidants.